Nursing Students, Faculty, and Preceptors Perception of Effective Characteristics of Clinical Instructor: A Cross-Sectional Study - Shmayil F. Buanz; Abrar Y. Alsenayien; Hanin A. Altharman; Rawan I. Alnaqi; Maria Blesilda B. Llaguno; Ola Mousa; Rayan A. Siraj (SAGE Publishing, 2024)
Background Nursing instructors play an important role in improving the clinical experience of nursing students. Despite this, little is known about the characteristics of effective clinical instructors. Objective Identifying the perceptions of nursing students, faculty, and preceptors of effective clinical instructors. Method A descriptive cross-sectional study was conducted using a convenience sample of nursing students, faculty, and preceptors from different nursing departments. Participants were invited to respond to sociodemographic and Nursing Clinical Teacher Effectiveness Inventory questionnaires from April 2022 to September 2022. The data were analyzed using descriptive and inferential statistics using SPSS. Result A total of 715 participants responded to the survey, of whom 510 were students. Students valued interpersonal relations (5.57 ± 1.261) as the most important clinical instructor characteristic, while nursing competence was perceived as the least important (5.51 ± 1.298). Faculty scored the highest mean in the evaluation subscale (6.21 ± 1.170) and the lowest in nursing competence (6.07 ± 1.221). Preceptors scored the highest mean in the evaluation subscale (5.98 ± 0.904) and the lowest in personality (5.80 ± 0.928). One-way ANOVA showed significant mean differences between the perceptions of nursing students, faculty, and preceptors in personality ( M : 5.54 vs. 6.10 vs. 5.80, respectively; p  < .001), evaluation ( M : 5.56 vs. 6.21 vs. 5.98; p  < .001), teaching ability ( M : 5.57 vs. 6.12 vs. 5.86; p  < .001), nursing competence ( M : 5.51 vs. 6.12 vs. 5.86; p  < .001), and interpersonal relationship ( M : 5.57 vs. 6.17 vs. 5.88; p  < .001). There were significant mean differences in students' perceptions across academic levels. Conclusion Students, faculty, and preceptors perceived effective clinical instructors' characteristics differently. Therefore, nursing schools should establish and promote a program to develop and promote unified, effective clinical teaching characteristics.